2021
DOI: 10.1186/s12872-020-01825-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypercholesterolemia and associated risk factors in Al-Kharj population, Saudi Arabia: a cross-sectional survey

Abstract: Background Hypercholesterolemia (HC) is an important precursor to many cardiovascular, cerebrovascular, and peripheral vascular diseases. A report conducted by the American Heart Association showed the prevalence of HC to be 11.9%, with around 28.5 million adults age ≥ 20 years having high cholesterol levels. This study aimed to evaluate the prevalence of HC and its associated risk factors among the general population of Al-Kharj, Saudi Arabia. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The country is eighth in the world in terms of incidence rate at 33.5 cases per 100,000 individuals [ 19 ]. Unfortunately, Alzahrani et al [ 20 ] have reported a rate of 33% of dyslipidemia among Saudi individuals. On the other hand, Alzahib and Altemani [ 13 ] have reported dyslipidemia in 66.5% of patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The country is eighth in the world in terms of incidence rate at 33.5 cases per 100,000 individuals [ 19 ]. Unfortunately, Alzahrani et al [ 20 ] have reported a rate of 33% of dyslipidemia among Saudi individuals. On the other hand, Alzahib and Altemani [ 13 ] have reported dyslipidemia in 66.5% of patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory data included fasting plasma glucose (FPG), fasting TG, and fasting total cholesterol (TC). We defined hypertriglyceridemia as fasting TG ≥150 mg/dL [9] and hypercholesterolemia defined as TC ≥200 mg/dL [14]. Cardiometabolic risk factors included high FPG, high blood pressure (BP), and high body mass index (BMI).…”
Section: Data Collectionmentioning
confidence: 99%
“…To date, different data-based studies were performed on the Indian population, including the India Migration Study ( n = 1983), India Heart Watch ( n = 6123), Indian Industrial Population Surveillance Study ( n = 10,442), Indian Women Health Study ( n = 4624), Indian Council of Medical Research (ICMR) Integrated Disease Surveillance Project (urban n = 15,223, slum/periurbann = 15,751, rural n = 13,517), a nationwide industry-sponsored FitHeart Study ( n = 46,919) and the INDIAB study ( n = 2042) [ 37 , 38 , 39 , 40 , 41 , 42 ]. Among those, Al-Kharj of Saudi Arabia showed a positive association between the prevalence of HC and increasing age in the general population [ 43 ]. Another study reported that overweight participants have a higher risk of suffering from HC.…”
Section: Hypercholesterolemiamentioning
confidence: 99%